Edukasi Dan Implementasi Asuhan Keperawatan Pada Pasien Asma Dan Manajemen Serangan Akut Di Lingkungan Rumah Tangga - Zaenal Zaenal; Rini Mustamin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Asthma is a chronic respiratory disease characterized by airway inflammation and narrowing, causing symptoms such as shortness of breath, coughing, wheezing, and chest tightness. Acute asthma attacks may occur suddenly and require prompt and appropriate management to prevent severe complications. Lack of family knowledge regarding early signs of attacks, proper medication use, and initial home management can worsen the patient's condition. This Community Service Program aimed to improve patients’ and families’ knowledge about acute asthma attack management through nursing care education at the household level. The activities included health education, inhaler technique demonstrations, education on trigger control, and evaluation using pre-test and post-test assessments. The program involved 35 asthma patients and family members in the primary healthcare service area. The results showed an increase in participants’ knowledge scores from 55.2 before education to 86.8 after education. Participants were also able to recognize warning signs of asthma attacks and understand appropriate initial management. This educational intervention was effective in improving family preparedness in managing asthma and preventing complications at home